Pengaruh Lingkungan Kerja Non-Fisk dan Kepuasan Kerja Terhadap Turnover Intention Karyawan pada PT Haleyora Powerindo Palembang - Sukarni Aprianinur; Endah Dewi Purnamasari; Mohammad Kurniawan DP (Universitas Batanghari Jambi, 2023)
The purpose of this research is to learn how PT Haleyora Powerindo Palembang's employees' perceptions of their non-physical work environment and their level of job satisfaction affect their likelihood of leaving the company. Distributing surveys with Google Form is a quantitative research method. Saturated sampling was used, in which all 43 respondents were included in the sample. Primary data was collected by a purposeful sampling strategy, while secondary data was gathered from other sources. The t test indicates that the effect size of Non-Physical Work Environment (X1) on Employee Turnover Intention (Y) is 0.000 0.05 (tcount = 4.974 > 5) and the sig value is Non-Physical Work Environment (X1) on Employee Turnover Intention (Y) is 0.01. This is table 2.021. Since the tcount value for Job Satisfaction (X2) on Employee Turnover Intention (Y) is 2.508 > 0.05 and the sig value for Job Satisfaction (X2) on Employee Turnover Intention (Y) is 0.048 < 0, 05, we may infer that Ho is false and Ha is true. This is table 2.021. Because of this positive or substantial influence of Job Satisfaction on Turnover Intention, we may rule out Ho and embrace Ha. Ho is rejected and Ha is accepted, indicating that the non-physical work environment (X1) and job satisfaction (X2) have a combined influence on employee turnover intention, as shown by the F test analysis, which reveals an Fcount of 16.889 and a Ftable value of 3.23. (Y).